Acid-labile hyperbranched poly(ortho ester amido amine) as efficient gene carriers: Preparation, characterization, and in vitro evaluation. (July 2019) - Li, Shuting; Hu, Liefeng; Wang, Jun; Yan, Guo; Wang, Xin; Li, Dapeng; Zeng, Xiaoli; Tang, Rupei
Cationic polymers have become one of the most promising synthetic vectors for gene transfection, however, their translation to the clinic has been severely hampered because of their high cytotoxicity and polyplex instability in serum. Herein, we report the design and synthesis of a new type of pH-sensitive hyperbranched poly(ortho ester amido amine) (HPOEAMAM) by the use of ortho ester bonds to give a non-viral vector with high efficiency and safety in two-dimensional (2D) cells and three-dimensional (3D) multicellular tumor spheroids. The pH-sensitive HPOEAMAM forms strong interactions with DNA and completely condense DNA at the weight ratio of 8. Furthermore, ortho ester in HPOEAMAM can be hydrolysed in response to endo/lysosome pHs to facilitate DNA release post internalization and diminish the cytotoxicity. Our findings provide a valuable insight into the construction of pH-sensitive hyperbranched cationic polymers which is an attractive strategy for producing effective gene vectors for clinically viable gene therapy.